Wiley Encyclopedia of Management 2015
DOI: 10.1002/9781118785317.weom010055
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Accounting Disclosures

Abstract: Narrative accounting disclosures are an integral part of the corporate financial reporting package. They are deemed to provide a view of the company “through the eyes of management”. The narratives represent management's construal of corporate events and are largely discretionary. Research in accounting narratives examines informational and presentational aspects of narrative financial reporting. Narrative accounting disclosures are studied from an informational perspective through usefulness surveys, predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Narrative corporate disclosure provides investors a view of the firm through the eyes of the management. With wide discretion on how to convey their message, textual disclosure enables management to offer context within which investors can interpret the firm's performance, financial position and more importantly management objectives in the periods ahead (Aerts 2015). Previous literature has shown that the features of textual disclosure, including readability and tone, have significant market implications (Lawrence 2013;Lehavy et al 2011;Loughran and Mcdonald 2011;Loughran and McDonald 2016).…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Narrative corporate disclosure provides investors a view of the firm through the eyes of the management. With wide discretion on how to convey their message, textual disclosure enables management to offer context within which investors can interpret the firm's performance, financial position and more importantly management objectives in the periods ahead (Aerts 2015). Previous literature has shown that the features of textual disclosure, including readability and tone, have significant market implications (Lawrence 2013;Lehavy et al 2011;Loughran and Mcdonald 2011;Loughran and McDonald 2016).…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%